Respiratory Sinus Arrhythmia and its Association with Pain in Women with Fibromyalgia Syndrome. Issue 6 (1st June 2015) - Zamunér, Antonio R; Forti, Meire; Andrade, Carolina P; Avila, Mariana Arias; da Silva, Ester
Abstract: Objectives: To assess the cardiac autonomic control at rest and during the deep breathing test (DBT) and its association with pain in women with fibromyalgia syndrome (FMS). Methods: The study included 20 women with FMS and 20 healthy women (control group, CG). The pain was quantified by assessing the pressure pain threshold (PPT), VAS of pain, and the pain component of the SF‐36 questionnaire. The RR intervals were recorded in the supine position and during the DBT. The heart rate variability (VHR) was measured by methods in the time and frequency domain. Results: The group with FMS had abnormal cardiac autonomic modulation at rest and during DBT, compared to CG ( P < 0.05). Positive correlations were found between PPT and the E/I ratio ( r = 0.70), ΔFC ( r = 0.66) and power spectrum density (DEP, r = 0.56) indices of DBT, as well as between pain component of the SF‐36 and the E/I ratio ( r = 0.49), ΔFC ( r = 0.45) and DEP ( r = 0.50) indices of DBT. Significant correlations were observed between the FIQ questionnaire and the LF/HF ratio index in the supine position and the E/I ratio ( r = −0.63), ΔFC ( r = −0.54), and DEP ( r = −0.51) indices of DBT. Conclusions: The results of VHR indices during the supine position and the DBT women with FMS suggest impairment of neurocardiac integrity associated with pain and the impact of FMS on the quality of life.